Effect of implantoplasty on the elastic limit of dental implants of different diameters - Markel Diéguez-Pereira; David Chávarri-Prado; Iratxe Viteri-Agustín; Oier Montalban-Vadillo; Esteban Pérez-Pevida; Aritza Brizuela-Velasco (SpringerOpen, 2021)
Abstract Background Implantoplasty reduces both implant diameter and the thickness of its walls, subsequently reducing the ability of the implant to resist fracture in response to functional load. In combination with an increase in the crown-implant ratio due to bone loss, this could increase the lever effect, which in presence of high masticatory forces or parafunctional habits, could lead to complications such as fracture of the implant or loosening of the prosthetic screw. Objectives To determine the elastic limits of internal connection, dental implants of different designs and diameters after an implantoplasty. Materials and methods This in vitro study included 315 tapered internal connection titanium dental implants, the threads of which were removed with an industrial milling machine-for standardized implantoplasty (IMP1; n = 105)-or with the conventional approach-manually, using high-speed burs (IMP2; n = 105). The remaining 105 implants were used as controls. The final implant diameters were recorded. The quality of the newly polished surfaces was assessed by scanning electron microscopy. All implants were subjected to a mechanical pressure resistance test. A Tukey's test for multiple comparisons was used to detect differences in the elastic limit and final implant diameters between the implant groups. Results There were statistically significant differences in the elastic limit between the IMP1, IMP2, and control groups (p < 0.05). Furthermore, the implant diameter was significantly smaller in the IMP1 and IMP2 groups (p < 0.05). Scanning electron microscopy revealed smooth implant surfaces in the IMP1 and IMP2 groups, with some titanium particles visible in the IMP1 group. Conclusions Implantoplasty significantly decreased the elastic limit of internal connection titanium dental implants, especially in those with a smaller diameter (3-3.5 mm).